Characterization of Phytoconstituents and Exploration of Antioxidant and Free Radical Scavanging Activities of Citrus assamensis Leaf - Shahriar, Mohammad; Bhuiyan, Mohiuddin Ahmed; Rana, Md Sohel (Dhaka University Journal of Pharmaceutical Sciences, 2018)
The aim of the current investigation was to identify bioactive secondary metabolites and compare the phytoconstituents and antioxidant profile of different leaf extracts of Citrus assamensis. Preliminary phytochemical screening of chloroform extract of C. assamensis indicated the presence of alkaloids, phytosterols, phenols, tannins, glycosides, saponins and flavonoids, whereas the methanol and ethanol extracts were found to contain no saponin. The screenings of the plant revealed that, the amount of phenols was higher in methanol extract, while the ethanol extract was found to be rich in flavonoid and total antioxidant capacity. Methanol extract of C. assamensis leaf showed potent nitric oxide and hydrogen peroxide scavenging activity having IC50 value of 137.85 and 85 μg/ml, respectively. The chloroform extract was found to be highly effective in DPPH free radical scavenging, reducing power, cupric reducing antioxidant capacity and superoxide dismutase activity when compared to the standard. In case of catalase assay, all the C. assemensis leaf extracts showed highest activity at 50μg/ml. In most cases, lowest concentration of test groups showed significant (**p<0.01 & *p<0.05) peroxidase activity. Dhaka Univ. J. Pharm. Sci. 17(1): 29-36, 2018 (June)